Talar fractures: radiological and CT evaluation and classification systems - Caracchini, Giuseppe; Pietragalla, Michele; De Renzis, Alioscia; Galluzzo, Michele; Carbone, Mattia; Zappia, Marcello; Russo, Anna; Greco, Federico; Miele, Vittorio (Acta Biomedica Atenei Parmensis, 2018)
Introduction: The talus is the second largest bone of the foot. It is fundamental to ensure normal ankle-foot movements as it connects the leg and the foot. Talar fractures are usually due to high energy traumas (road accidents, high level falls). They are not common as they account for 3-5% of ankle and foot fractures and 0.85% of all body fractures. However, talar fractures not correctly diagnosed and treated can lead to avascular necrosis of the astragalus, pseudoarthrosis, early osteoarthrisis and ankle instability, declining the quality of life of patients. Methods: A PubMed search was performed using the terms “talus” “talus AND radiology”, “talar fractures”, and “talar fractures classification”, selecting articles published in the last 98 years. We selected articles about pre-treatment and post-surgery talar fractures diagnostic imaging. We also selected articles about talar fractures complications and traumatic talar dislocations. Case reports have not been included. Aim of the work: to describe radiological evaluations, classification systems, and biomechanical patterns involved in talar fractures. Also we will briefly describe talar fractures complications and treatment option and strategies. Conclusions: This work suggests a radiological approach aimed to classify talar fractures and guide treatment strategies, improving patient outcomes.